Does venture capital affect crowdfunding performance? - Chia-ling Chang; Yen-Sheng Lee; Han-Kun Tien (Economic Review: Journal of Economics and Business, 2021)
This study quantitatively discusses the relationship among venture capitalists, entrepreneurs, and crowdfunders. It considers the effectiveness of venture capital on the performance of crowdfunding campaigns started by entrepreneurs. Specifically, we split 274,220 crowdfunding projects into venture capital- and non-venture capital-funded projects and examined whether this type of financing enhances the performance of crowdfunding campaigns-measured by the number of crowdfunders and the amount of proceeds raised by the crowdfunding campaigns. The results of linear regression models reveal that the venture capital- funded entrepreneurial firms perform better in the crowdfunding market than their non-funded peers. Value-added services of the venture capital firms intensify the visibility of venture capital-financed startups in the crowdfunding market, thereby elevating crowdfunding performance. This study can help venture capital-backed entrepreneurs planning to launch crowdfunding campaigns gain an understanding of the role of venture capital in crowdfunding performance.
Keywords: G24; 330; venture capital; crowdfunding performance; entrepreneurs